THE EFFECTIVENESS OF THE USE OF CHEMCOLLECTIVE VIRTUAL LABORATORY MEDIA WITH GUIDED INQUIRY LEARNING MODELS ON STUDENT LEARNING OUTCOMES ON ACID-BASE TITRATION MATERIAL - Theresia, Clara; Hartati, Yuli; Lestari, Sri (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
This study aims to determine the effectiveness of using ChemCollective virtual laboratory media with guided inquiry learning models on student learning outcomes on acid-base titration material. The subjects of this study were XI MIA 1 and XI MIA 2 classes totaling 59 students. The research subjects were selected using saturated sampling technique. This research method is pre-experiment with one group pretest-posttest design. Data collection used tests in the form of pre-test and post-test and student response questionnaires which were then analyzed using the N-Gain test and effect size test. The results showed that the use of virtual laboratory media was effective for improving student learning outcomes with an N-Gain value of 0.5022 which was classified as moderate and the level of effectiveness was classified as very strong with an effect size value of 1.5716. Keywords: Effectiveness, Virtual Laboratory, Learning Outcomes, Acid-Base Titration